The impact of the increasing burden of trauma in Malawi on orthopedic trauma service priorities at Kamuzu Central Hospital. (1st November 2016) - Young, Sven; Banza, Leonard; Munthali, Boston S; Manda, Kumbukani G; Gallaher, Jared; Charles, Anthony
Abstract : Background and purpose — The burden of road traffic injuries globally is rising rapidly, and has a huge effect on health systems and development in low- and middle-income countries. Malawi is a small low-income country in southeastern Africa with a population of 16.7 million and a gross national income per capita of only 250 USD. The impact of the rising burden of trauma is very apparent to healthcare workers on the ground, but there are very few data showing this development. Patients and methods — The annual number of femoral fracture patients admitted to Kamuzu Central Hospital (KCH) in the Capital of Malawi, Lilongwe, from 2009 to 2014 was retrieved from the KCH trauma database. Linear regression curve estimation was used to project the growth in the burden of femoral fractures and the number of operations performed for femoral fractures over the same time period. Results — 992 patients with femoral fractures (26% of all admissions for fractures) presented at KCH from 2009 through 2014. In this period, there was a 132% increase in the annual number of femoral fractures admitted to KCH. In the same time period, the total number of operations more than doubled, but there was no increase in the number of operations performed for femoral fractures. Overall, there was a 7% mortality rate for patients with femoral fractures. Interpretation — The burden of femoral fractures in Malawi is rising rapidly, and the surgical resources available cannot keep up with this development. Limited funds for orthopedic trauma care in Malawi should be invested in central training hospitals, to develop a sustainable number of orthopedic surgeons and improve current infrastructure and equipment. The centralization of orthopedic surgical care delivery at the central training hospitals will lead to better access to surgical care and early return of patients to local district hospitals for rehabilitation, thus increasing surgical throughput and efficiency in a more cost-effective manner, with the goal of expanding the future orthopedic surgical workforce to meet the national need.